Der Bundespräsident. Briefe 1954-1959 - Heuss, Theodor (Briefe, 2014)
Theodor Heuss assumed his second term of office as President of Germany in September 1954 under propitious circumstances: He was re-elected by an overwhelming majority in the Federal Assembly, and enjoyed surprisingly broad public approval. His non-partisan style of leadership allowed him to win the support of Germany`s citizenry for key political decisions. As a representative abroad he presented Germany in a new light, showcasing it as a decidedly democratic, peaceful, and civil society.